Infectious Aortitis with Abdominal Aortic Aneurysm in a 47-Year-Old Female with Systemic Lupus Erythematosus - Valerie R. Ramiro; Carmegie C. Saliba; John Anthony D. Tindoc; Marinette R. Jambaro; Enrique M. Chua; Donna Ricca M. Hornilla; Maria Teresa B. Abola (Case Reports in Cardiology)
Aortic aneurysms are not commonly reported among patients with systemic lupus erythematosus (SLE). We report a case of a 47-year-old Filipino female diagnosed with SLE 17 years ago maintained on prolonged oral steroids, azathioprine, and hydroxychloroquine. She also had lupus nephritis, secondary hypertension, and dyslipidemia. She initially presented with a week-long watery nonbloody diarrhea with associated diffuse crampy abdominal pain and generalized weakness. She was admitted for a week at a provincial hospital and was given an unrecalled antibiotic with resolution of symptoms. Upon discharge, however, she experienced two weeks of severe right lower quadrant pain radiating to the back and left lower quadrant, with no history of diarrhea, vomiting, dysuria, and fever. Complete blood count showed slight leukocytosis and elevated C-reactive protein. Abdominal imaging revealed a saccular infrarenal aneurysm with dissection. An atherosclerotic mechanism was primarily considered, but a vasculitic process was likewise considered due to elevated acute phase reactants. The initial plan was Endovascular Aneurysm Repair (EVAR) but due to financial limitations, an exploratory laparotomy with infrarenal endoaneurysmorrhaphy was eventually performed. Intraoperative findings were a saccular infrarenal aneurysm with dissection up to the proximal right common iliac artery and an abscess compartment within the false lumen in the anterior aortic wall. Abscess culture yielded high growth of Salmonella group B. Micrographs of the aortic wall biopsy showed fibrin deposition necrosis and calcification with peripheral viable cellular infiltrates consisting of neutrophils and foamy macrophages. Inadvertently placing an endovascular graft in an infected aortic aneurysm would have led to graft infection and catastrophic morbidity. We highlight the significance of having a high index of suspicion for infectious causes of aortitis among immunocompromised patients presenting with aneurysm prior to pursuing an endovascular versus an open approach for repair.